Expression of risk genes linked to vitamin D receptor super-enhancer regions and their association with phenotype severity in multiple sclerosis - Orton, Sarah M.; Sangha, Amarpreet; Gupta, Mehul; Martens, Kristina; Metz, Luanne M.; de Koning, A. P. J.; Pfeffer, Gerald (Frontiers in Neurology, 2022)
Multiple sclerosis (MS) is a chronic debilitating neurological condition with a wide range of phenotype variability. A complex interplay of genetic and environmental factors contributes to disease onset and progression in MS patients. Vitamin D deficiency is a known susceptibility factor for MS, however the underlying mechanism of vitamin D-gene interactions in MS etiology is still poorly understood. Vitamin D receptor super enhancers (VSEs) are enriched in MS risk variants and may modulate these environment-gene interactions. mRNA expression in total of 64 patients with contrasting MS severity was quantified in select genes. First, RNA-seq was performed on a discovery cohort (10 mild, 10 severe MS phenotype) and ten genes regulated by VSEs that have been linked to MS risk were analyzed. Four candidates showed a significant positive association (GRINA, PLEC, PARP10, and LRG1) in the discovery cohort and were then quantified using digital droplet PCR (ddPCR) in a validation cohort (34 mild, 10 severe MS phenotype). A significant differential expression persisted in the Validation cohort for three of the VSE-MS genes: GRINA (p = 0.0138), LRG1 (p = 0.0157), and PLEC (p =0.0391). In summary, genes regulated by VSE regions that contain known MS risk variants were shown to have differential expression based on disease severity (p<0.05). The findings implicate a role for vitamin D super enhancers in modulating disease activity. In addition, expression levels may have some utility as prognostic biomarkers in the future.